Coop yata 'to - Aguilar, Mila D.; Tiongson, Lito; Albano, Judith; Roque, Andrew; Zapanta, Noel (Pinoy Tok, 1988)
A basic introduction to cooperatives. It features three different coops with various degrees of success: the famed multi-million Baclaran Market Vendors Cooperative, a farmers' coop in Cabiao, Nueva Ecija, and a starting fishermen's coop in Aplayang Munti, Cavite.